Herbal Milliherb Development since 1999 - 2004-2014 - Azis, Sriana (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The formula Milliherb consists of more than 25 herbs (similar effect) of approximately 70 % vegetable, fruit, spices and 30 % nontoxic Indonesian herbs. Milliherb Medicine that is efficacy similar or more than modern drugs, medicine specific diseases, safe, cost effective, and affordable as a solution for many of our nations health care problem. Hypothesis: mix herbs, small dose (500 mg dry herbs), synergistic (> 800 times), increase the blood flow, and as the body system are in balance. In some cases observed, these medicines have the efficacy of approximately 90 %, or more and have no adverse reaction, with relatively small doses used. Obyective All diseases have drugs and all disease is curable Result Milliherb produces 29 preparation (2004). Medicines consists of 16 products for treatment diseases and 13 products for health promotion. In 2014 it was produces 40 preparation. MILLIHERB used to heal various illness, both incurable illness. The preparations of Milliherb used to treat and / or alleviate pain , gout , uric acid, inflammation, Xgra, women, obesity; antidote (narcotics, smoking); asthma, cough, bronchitis, tuberculosis, cikungunyah, dengue, herpes (another virus infection), constipation and hemorrhoids, cholesterol, hypertension & diabetes, liver diseases, gallstones & hepatitis ABC; pain heart, kidney stones & nephritis, prostate, gastric, intestine & ulcus, anemia, thallassemia and leukemia, brain tonic, eye tonic, skin diseases and acne, leprosy, warts, rheumatism, HIVAIDS, and even for the treatment of tumors & cancer, cirrhosis, lupus , fillariasis, thyroid, ect